Determinants of cross-selling opportunities impacting customer lifetime value at Runner Automobile PLC - Hossain, Mokammel (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.